Detection of Interfractional Morphological Changes in Proton Therapy: A Simulation and In Vivo Study With the INSIDE In-Beam PET - Fiorina, Elisa; Ferrero, Veronica; Baroni, Guido; Battistoni, Giuseppe; Belcari, Nicola; Camarlinghi, Niccolo; Cerello, Piergiorgio; Ciocca, Mario; De Simoni, Micol; Donetti, Marco; Dong, Yunsheng; Embriaco, Alessia; et al. (Frontiers in Physics, 2021)
In particle therapy, the uncertainty of the delivered particle range during the patient irradiation limits the optimization of the treatment planning. Therefore, an in-vivo treatment verification device is required, not only to improve the plan robustness, but also to detect significant inter-fractional morphological changes during the treatment itself. In this paper, an effective and robust analysis to detect regions with a significant range discrepancy is proposed. This study relies on in-vivo treatment verification by means of in-beam Positron Emission Tomography (PET) and was carried out with the INSIDE system installed at the National Centre of Oncological Hadrontherapy (CNAO) in Pavia, which is under clinical testing since July 2019. Patients affected by head-and-neck tumors treated with protons have been considered. First, in order to tune the analysis parameters, a Monte Carlo (MC) simulation was carried out to reproduce a patient who required a replanning because of significant morphological changes found during the treatment. Then, the developed approach was validated on the experimental measurements of three patients recruited for the INSIDE clinical trial (ClinicalTrials.gov ID: NCT03662373), showing the capability to estimate the treatment compliance with the prescription both when no morphological changes occurred and when a morphological change did occur, thus proving to be a promising tool for clinicians to detect variations in the patients treatments.